Eye structure, activity rhythms, and visually-driven behavior are tuned to visual niche in ants - Yilmaz, Ayse; Aksoy, Volkan; Camlitepe, Yilmaz; Giurfa, Martin (Frontiers in Behavioral Neuroscience, 2014)
Insects have evolved physiological adaptations and behavioural strategies that allow them to cope with a broad spectrum of environmental challenges and contribute to their evolutionary success. Visual performance plays a key role in this success. Correlates between life style and eye organization have been reported in various insect species. Yet, if and how visual ecology translates effectively into different visual discrimination and learning capabilities has been less explored. Here we report results from optical and behavioural analyses performed in two sympatric ant species, Formica cunicularia and Camponotus aethiops. We show that the former are diurnal while the latter are cathemeral. Accordingly, F. cunicularia workers present compound eyes with higher resolution, while C. aethiops workers exhibit eyes with lower resolution but higher sensitivity. The discrimination and learning of visual stimuli differs significantly between these species in controlled dual-choice experiments: discrimination learning of small-field visual stimuli is achieved by F. cunicularia but not by C. aethiops, while both species master the discrimination of large-field visual stimuli. Our work thus provides a paradigmatic example about how timing of foraging activities and visual environment match the organization of compound eyes and visually-driven behaviour. This correspondence underlines the relevance of an ecological/evolutionary framework for analyses in behavioural neuroscience.